Continuous Laryngeal Adductor Reflex Versus Intermittent Nerve Monitoring in Neck Endocrine Surgery. (4th May 2020) - Sinclair, Catherine F.; Téllez, Maria J.; Ulkatan, Sedat
Abstract : Objective: Intraoperative neuromonitoring (IONM) techniques aim to identify and potentially prevent nerve injury during surgeries. Prior studies into the efficacy of recurrent laryngeal nerve (RLN) IONM convey mixed results, with some claiming equivalence between IONM and no monitoring at all. The goal of the current study was to compare continuous RLN monitoring using the laryngeal adductor reflex (LAR) to intermittent RLN monitoring (intermittent IONM) to determine whether continuous monitoring reduces the incidence of intraoperative RLN injury during neck endocrine surgeries. Methods: In this observational, historical case‐control study, a historical cohort of patients monitored with intermittent‐IONM (group 1, n = 130) were compared to prospectively collected data from consecutive nerves‐at‐risk monitored continuously with the LAR (LAR‐CIONM, group 2, n = 205), at a single center by a single surgeon. The test benefit ratio and relative risk reduction (RRR) for LAR‐CIONM over intermittent IONM were calculated. Results: For group 1, nine nerves at risk exhibited intraoperative LOS with transient postoperative vocal fold (VF) hypomobility (n = 2) or immobility (VFI, n = 7). For group 2, two nerves at risk (0.98%) had sudden intraoperative LAR LOS following bipolar cautery, resulting in postoperative transient VFI ( P = .004). In each group, there was one case of permanent postoperative VFI. The test benefit rate ratio for LAR‐CIONM demonstrated a dramatic effect at 5.23, with an RRR of 81.0%. Conclusion: LAR‐CIONM significantly decreased rates of postoperative transient VF paralysis and paresis over intermittent IONM alone ( P = .004). Surgeons should be aware of the benefits and limitations of intermittent IONM versus CIONM. Intermittent IONM, although useful in nerve mapping and intraoperative decision making, has minimal benefit for the prevention of nerve injury, whereas CIONM can potentially reduce nerve injury rates and improve patient outcomes. Level of Evidence: 3 Laryngoscope, 131:230–236, 2021